Mythology and Theological Language - McLelland, Joseph C. (Scottish journal of theology, 1958)
Daniel Lamont, I think it was, once remarked that theologians should read more poetry. This insight into the nature of theological language has profound relevance for our contemporary concern with the problem of communicating the Gospel to modern man. Theology, as language about God, may be regarded in one sense as faced with an impossible task: ‘The maker and father of this Universe it is difficult to discover; nor, if he were discovered, could he be declared to all men.’ This hiddenness of the divine being is reflected even in the historical beginnings of the biblical revelation, in the cryptic tautology, ‘I am that I am’ (Exod. 3.14). Yet the fact of revelation was taken to mean, within Israel at least, not that the divine aseity was now compromised, but that this very self-sufficiency was revealed in terms of a purpose of love towards this people. The revelation was instrumental to the fulfilment of that purpose: the divine condescension used creaturely forms to communicate its truth and life to men. Therefore the theological language which sets forth this communicative revelation will be proportionately indirect or analogical.